Papillary Adenocarcinoma of Rete Testis Mimics Inflammatory Lump: A Case Report - Che-An Wu; Yung-Hsiang Chen; Kee-Ming Man; Jui-Lung Shen; Wen-Chi Chen (Case Reports in Urology)
We presented a rare extratesticular neoplasm, papillary adenocarcinoma of rete testis, which manifested variable symptoms and mimicked most frequently seen benign extratesticular lesions. Due to its rarity, the treatment is therefore uncertain. Our patient's clinical manifestations mimicked an inflammatory lump and underwent radical orchiectomy after pathological report had been confirmed. Unlike other reports, our patient survives and has a good outcome. No definite predictor and tumor marker can be used to define the prognosis. Early diagnosis and surgical treatment may have a good outcome.